Rural-rural migration, land and labor markets in Zambia - Chamberlin, J.; Sitko, N.; Jayne, T. (2018)
While the bulk of migration literature in Africa has focused on the movement of people from rural to urban areas, much less is known about rural mobility, including its magnitude, drivers, and implications for agricultural development. Using nationally representative survey data for Zambia, we document very high levels of rural mobility throughout the country, and show that this movement is correlated with both land and labor market conditions. About 20% of rural households on average have moved from elsewhere, with highest in-migration rates (~30%) in more accessible, higher density areas, reflecting the importance of wage-employment and services as pull factors. We find that rural in-migrants in relatively accessible areas are wealthier than in-migrants in less accessible areas, although in-migrants are wealthier than non-migrants in all areas. Furthermore, rural in-migrants exhibit greater use of inputs, agricultural productivity, land use intensity and market integration than their non-migrant neighbors. Impacts of in-migration on receiving communities appear to be virtuous: in addition to descriptive indicators that indicate cash injections into local economies (e.g. via greater propensity to hire in labor and services), we find econometric evidence of positive spillover effects of neighborhood in-migration rates on farm-level land productivity outcomes.